2000
DOI: 10.1128/jcm.38.2.800-806.2000
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Sensitivity of High Levels of Immunoglobulin G Antibodies against Pertussis Toxin in a Single Serum Sample for Diagnosis of Infection with Bordetella pertussis

Abstract: Laboratory confirmation of pertussis by culture, PCR, or detection of antibody increase in paired sera is hampered by low sensitivity in the later stages of the disease. Therefore, we investigated whether, and at which level, concentrations of immunoglobulin G (IgG) antibodies against pertussis toxin (PT), IgG-PT, in a single serum sample are indicative of active or recent pertussis. IgG-PT, measured by enzyme-linked immunosorbent assay in units per milliliter, was analyzed in 7,756 sera collected in a populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
107
3
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(119 citation statements)
references
References 29 publications
(49 reference statements)
3
107
3
5
Order By: Relevance
“…Another study was done without age limit in a mostly vaccinated population (Netherlands) using a cutoff of ∼125 EU/ml (99th percentile of population). The study found a sensitivity of 76.4%, whereas a cutoff ∼62 EU/ml (∼95th percentile of population) had a sensitivity of 88.8% [61].…”
Section: Serodiagnosis Of B Pertussis In Different Countriesmentioning
confidence: 80%
See 3 more Smart Citations
“…Another study was done without age limit in a mostly vaccinated population (Netherlands) using a cutoff of ∼125 EU/ml (99th percentile of population). The study found a sensitivity of 76.4%, whereas a cutoff ∼62 EU/ml (∼95th percentile of population) had a sensitivity of 88.8% [61].…”
Section: Serodiagnosis Of B Pertussis In Different Countriesmentioning
confidence: 80%
“…The cutoff point was set at 20 g/ml, which is equivalent to 200 CBER units per ml. This is actually quite high relative to what other groups have chosen [58,61].…”
Section: Serodiagnosis Of B Pertussis In Different Countriesmentioning
confidence: 81%
See 2 more Smart Citations
“…A patient was considered positive for an acute B. pertussis infection (infection in the last 6 months) if positive by PCR in a respiratory sample and/or the presence of an antibody titre to pertussis toxin of !125 IU/mL in convalescent serum (days 28e35), demonstrated previously as a cut-off with high sensitivity and specificity [8,9].…”
Section: Diagnostic Criteriamentioning
confidence: 84%